From Chaucer to the Restoration: A Comparative Analysis of Elizabethan Drama and Literature in the Artificial Intelligence Era - Baskota, Prateet (SXC Journal, 2025)
This research article explores the literature and drama of the Elizabethan period, spanning from the works of Geoffrey Chaucer to the Restoration drama with comparative analysis till 2023. The Elizabethan period was a time of great artistic and cultural flourishing in England, and produced some of the most influential and enduring works of literature and drama in the English language. The article examines the major literary and dramatic trends of the period, including the development of the English sonnet, the rise of the theatre, and the emergence of new genres such as the revenge tragedy and the pastoral. It also examines the works of some of the most important authors and playwrights of the period, including William Shakespeare, Christopher Marlowe, and Ben Jonson, with different bibliographical entries from all around the world, from Chaucer to the Artificial Intelligence era.